2013
DOI: 10.4314/njp.v40i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease: An unusual presentation in a 14-year old boy in Sokoto, north western Nigeria

Abstract: Kawasaki disease (KD) is an acute systemic vasculitis that mostly affects children less than 5years. Occasionally, it may presents with renal involvement of varying severity. In Nigeria and most of Africa, only a few cases of KD have been reported and these were among children within the typical age group. We report an unusual case of Kawasaki disease with renal manifestation in a 14 year old adolescent. Apart from the principal features of KD comprising of high grade fever, non purulent conjunctivitis, polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…While one of the patients was within the at-risk-age-group, the other patient was diagnosed at an atypical age of 14 years. [25] The latter case further confirmed the fact that KD can occur even in older age groups. [26] A significant observation in this study is that all the patients with EMF were boys, which is similar to findings from a recent study in Nigeria.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…While one of the patients was within the at-risk-age-group, the other patient was diagnosed at an atypical age of 14 years. [25] The latter case further confirmed the fact that KD can occur even in older age groups. [26] A significant observation in this study is that all the patients with EMF were boys, which is similar to findings from a recent study in Nigeria.…”
Section: Discussionsupporting
confidence: 55%
“…As previously highlighted, the only two cases of KD in this study included an unusual case in a 14-year-old boy that was the first reported case from our center; [25] and a second case in a 2.5-year-old boy who had all the features of KD in association with abnormal hematologic profile and right coronary artery aneurysm. It has been shown that coronary artery abnormalities occurs in 25% of patients with KD and is the most serious sequale that can result in significant morbidity and mortality.…”
Section: Discussionmentioning
confidence: 85%
“…In this present case, bilateral redness of the eyes, redness of tongue, a swelling on the cervical region (possibly lymphadenopathy) and desquamation of the skin around the perianal region had disappeared prior to presentation. The manifestation of periungual desquamation later on admission is also in keeping with reported sequential manifestation of symptoms that can occur in Kawasaki disease (6) (Figure 3). …”
Section: Discussionsupporting
confidence: 65%
“…Kawasaki disease, especially the non-classical form, poses a diagnostic dilemma and at times, not all clinical features required to make the diagnosis are present at the same time (6). In this present case, bilateral redness of the eyes, redness of tongue, a swelling on the cervical region (possibly lymphadenopathy) and desquamation of the skin around the perianal region had disappeared prior to presentation.…”
Section: Discussionmentioning
confidence: 67%
“…Coronary artery abnormality (CAA) was observed in three out of their eight patients or 37.5% of cases [ 22 ]. There have also been a few other patients with KD in Sub-Saharan Africa reported, notably from Ghana [ 23 ], Nigeria [ 24 , 25 ], and Madagascar [ 26 ].…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%